Expressing diminutive meaning in heritage Spanish: linking the heritage experience to diminutive use in everyday speech - Cruz, Abel (Frontiers in Language Sciences, 2024)
Introduction This paper studies the pragmatic force that heritage speakers may convey through the use of the diminutive in everyday speech. In particular, I analyze the use of the Spanish diminutive in 49 sociolinguistic interviews from a Spanish–English bilingual community in Southern Arizona, U.S. where Spanish is the heritage language. I compare the use of the diminutive in heritage Spanish to the distribution of the diminutive in the speech of a Spanish monolingual community (18 sociolinguistic interviews) from the same dialectal region. Although Spanish and English employ different morphosyntactic strategies to express diminutive meaning, the analysis reveals that the diminutive morpheme -ito/a is a productive morphological device in the Spanish-discourse of heritage speakers from Southern Arizona (i.e., similar diminutive distributions to their monolingual counterparts). While heritage speakers employed the diminutive -ito/a to express the notion of “smallness” in their Spanish-discourse, the analysis indicates that these language users are more likely to invoke a subjective evaluation through the diminutive -ito/a when talking about their family members and/or childhood experiences. This particular finding suggests that the concept “child” is the semantic/pragmatic driving force of the diminutive in heritage Spanish as a marker of speech by, about, to, or with some relation to children. The analysis further suggests that examining the pragmatic dimensions of the diminutive in everyday speech can provide important insights into how heritage speakers encode and create cultural meaning in their heritage languages. Methods In this study, I analyze the use of Spanish diminutives in two U.S.-Mexico border regions. The first data set is representative of a Spanish–English bilingual community in Southern Arizona, U.S., provided in the Corpus del Español en el Sur de Arizona (The CESA Corpus). The CESA Corpus comprises 49 sociolinguistic interviews of ~1 h each for a total of ~305,542 words. The second data set comprises 18 sociolinguistic interviews of predominantly monolingual Spanish speakers from the city of Mexicali, Baja California in Mexico, provided in the Proyecto Para el Estudio Sociolingüístico del Español de España y de América (PRESEEA). The Mexicali data set consists of ~119,162 words. Results The analysis revealed that the Spanish diminutive morpheme -ito/a is a productive morphological device in the Spanish-discourse of heritage speakers from Southern Arizona. In addition to its prototypical meaning (i.e., the notion of “smallness”), the diminutive morpheme -ito/a conveyed an array of pragmatic functions in the everyday speech of Spanish heritage speakers and their monolingual counterparts from the same dialectal region. Importantly, these pragmatic functions are mediated by speakers' subjective perceptions of the entity in question. Unlike their monolingual counterparts, heritage speakers are more likely to invoke a subjective evaluation through the diminutive -ito/a when talking about their family members and/or childhood experiences. Altogether, the study suggests that the concept “child” is the semantic/pragmatic driving force of the diminutive in heritage Spanish as a marker of speech by, about, to, or with some relation to children. Discussion In this study, I followed Reynoso's framework to study the pragmatic dimensions of the diminutive in everyday speech, that is, speakers' publicly conveyed meaning. The analysis revealed that heritage speakers applied most of the pragmatic functions and their respective values observed in Reynoso's cross-dialectal study of Spanish diminutives, and hence providing further support for her framework. Similarly, the study provides further evidence to Jurafsky's proposal that morphological diminutives arise from semantic or pragmatic links with children. Finally, the analysis indicated that examining the semantic/pragmatic dimensions of the diminutive in everyday speech can provide important insights into how heritage speakers encode and create cultural meaning in their heritage languages, which can in turn have further ramifications for heritage language learning and teaching.